Coexistence of psoriasis and vitiligo. (Colombia Medica, 2008)
We present a 53-years old male with a 10 years history of vitiligo who further developed psoriatic lesions clearly representing a Koebner´s phenomenon. He is currently being treated with phototherapy and narrowband UVB with an interin satisfactory outcome especially in the psoriasis.